A graph modeling framework to design and plan the downstream oil supply chain. (22nd March 2021) - Lima, Camilo; Relvas, Susana; Barbosa‐Póvoa, Ana
Abstract: In this paper, a deterministic mixed‐integer linear programming (MILP) model is proposed aiming at designing and planning the downstream oil supply chain. The optimization model defines the strategic network design, and then determines its tactical distribution plan. A multimodal transportation network is considered in which road, maritime, rail, and pipeline resources may be chosen. The network structure is represented through a graph modeling approach, so the diverse network operations, for example, the exchange of products between warehouses, may be readily incorporated into the optimization model. A case study based on the Brazilian oil industry is explored and analyzed to check and demonstrate the adequacy of the MILP model to solve a real‐world problem.